2012
DOI: 10.1099/ijs.0.032953-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhodoligotrophos appendicifer gen. nov., sp. nov., an appendaged bacterium isolated from a freshwater Antarctic lake

Abstract: A Gram-stain-negative, non-spore-forming, non-motile, irregularly circular, aerobic/microaerobic appendaged bacterium (strain 120-1 T ) was isolated from Naga-ike, one of the freshwater lakes in the Skarvsnes ice-free area of Antarctica. Strain 120-1 T grew between 5 and 35 6C, with optimum growth at 30 6C. The pH range for growth was between 6.0 and 9.0 (optimum of approximately pH 7.0). The range of NaCl concentration allowing growth of strain 120-1 T was between 0 and 5.0 %, with an optimum of 0.5-1.0 %. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain MA2 T was affiliated with the order Rhizobiales in the class Alphaproteobacteria (). Closely related species with validly published names were Rhodobium orientis (Hiraishi et al , 1995) (93.0 % sequence similarity), Parvibaculum hydrocarboniclasticum (Rosario-Passapera et al , 2012) (92.4 % similarity) and Rhodoligotrophos appendicifer (Fukuda et al , 2012) (92.1 % similarity). Strain MA2 T was distantly related to other stalked bacteria such as Caulobacter crescentus , Maricaulis maris and Oceanicaulis alexandrii ().…”
mentioning
confidence: 99%
“…Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain MA2 T was affiliated with the order Rhizobiales in the class Alphaproteobacteria (). Closely related species with validly published names were Rhodobium orientis (Hiraishi et al , 1995) (93.0 % sequence similarity), Parvibaculum hydrocarboniclasticum (Rosario-Passapera et al , 2012) (92.4 % similarity) and Rhodoligotrophos appendicifer (Fukuda et al , 2012) (92.1 % similarity). Strain MA2 T was distantly related to other stalked bacteria such as Caulobacter crescentus , Maricaulis maris and Oceanicaulis alexandrii ().…”
mentioning
confidence: 99%
“…Strain 120-1 T grows between 5 and 35 • C, with an optimum temperature of 30 • C. The OD 660 reaches a maximum value of about 1.2 after incubation for about 120 h. Other features of strain 120-1 T were described in detail in our recent study. 52 S120-1 DNA was extracted by the following procedures. Strain 120-1 T was cultivated in 0.25 × Luria-Bertani medium (2.50 g/l of tryptone, 1.25 g/l of yeast extract, 5.0 g/l of NaCl, pH 7) at 30 • C for 5 days with gentle shaking.…”
Section: A Materialsmentioning
confidence: 99%
“…4,38,51 Here, we extended our investigation to a megabase-size genomic DNA (S120-1 DNA) that was successfully extracted from Rhodoligotrophos appendicifer (strain 120-1 T = JCM 16873 T = ATCC BAA 2115 T ). 52 Strain 120-1 T was isolated from a freshwater lake in Antarctica and is characterized by slow growth and low rates of metabolism associated with its oligotrophic environment. Both of these features may enable us to successfully isolate large genomic DNA fragments of near-megabase size.…”
Section: Introductionmentioning
confidence: 99%
“…The G+C content of the genomic DNA, respiratory quinone, fatty acids and polar lipids pattern were analysed by previously described methods with slight modification (Fukuda et al , 2012; Yamada, et al , 2011). The fatty acids composition was analysed by the Sherlock Microbial Identification System using version 6.0 of the TSBA6 library.…”
mentioning
confidence: 99%